Novel Method of Estimating Iron Loss Equivalent Resistance of Laminated Core Winding at Various Frequencies - Maxime Colin; Thierry Boileau; Noureddine Takorabet; Stéphane Charmoille (Energies)
Electromagnetic and magnetic devices are increasingly prevalent in sectors such as transportation, industry, and renewable energy due to the ongoing electrification trend. These devices exhibit nonlinear behavior, particularly under signals rich in harmonics. They require precise and appropriate modeling for accurate sizing. Identifying model-specific parameters, which depend on frequency, is crucial. This article focuses on a specific frequency range where a circuit model with series resistance and inductance, along with a parallel resistance to account for iron losses (<semantics>Riron</semantics>), is applicable. While the determination of series elements is well documented, the determination of <semantics>Riron</semantics> remains complex and debated, with traditional methods neglecting operating conditions such as magnetic saturation. To address these limitations, an innovative experimental method is proposed, comprising two main steps: determining the complex impedance of the magnetic device and extracting <semantics>Riron</semantics> from the model. This method aims to provide a more precise and representative estimation of <semantics>Riron</semantics>, improving the reliability and accuracy of electromagnetic and magnetic device simulations and designs. The obtained values of the iron loss equivalent resistance are different by at least 300% than those obtained by an impedance analyzer. The proposed method is expected to advance the understanding and modeling of losses in electromagnetic and magnetic devices, offering more robust tools for engineers and researchers in optimizing device performance and efficiency.